Fikrah Tammām Ḥassān fī Taʿallum al-Lughah al-ʿArabiyyah li al-Nāṭiqīn bi Ghayrihā (Dirāsah Waṣfiyyah Taḥlīliyyah) - Dihyatun Masqon (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Tammām Ḥassān’s concept of Arabic language learning for non-native speakers is structured into three sequential stages: recognition (taʿarruf), comprehension (istiʿāb), and appreciation (istimtāʿ). The first stage, recognition, emphasizes three fundamental linguistic disciplines that form the basis of Arabic language instruction: phonetics, morphology, and syntax. Phonetics serves as the essential foundation for learning morphology and syntax. The second stage, comprehension, enables learners to understand various sentence patterns and distinguish between their different structures. This stage encompasses two dimensions: cultural meaning and linguistic, rhetorical, and stylistic meaning. The final stage, appreciation, is achieved only after learners have recognized the linguistic structures of a text and comprehended its meanings. At this stage, learners develop literary appreciation and the ability to perceive the aesthetic qualities and artistic beauty of Arabic texts.